Researcher – Andragogue in Qualitative Research: What is the Researcher’s Role in the Research Activities? - Golonka-Legut, Joanna; Pryszmont, Martyna (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Subject of this paper is part of the discussion on being a Qualitative Researcher.The content presented answers the questions: Who are andragogue researchers? What isthe researcher’s role in the research activities? What kind of researchers are/should theybe in the research they conduct? The first part of the text contains reflections on the characteristicsof a qualitative researcher and the researcher’s philosophical workshop. Next, wepay attention to the specificity of being a researcher and the role of the researcher andragoguein qualitative research from the perspective of various paradigmatic traditions. Then,we discuss the essence of reflexivity, which is the presented concept understood as thesource and space being a researcher in the qualitative approach. In the text, we also valueother features of a qualitative researcher: subjectivity, autonomy, the use of self-observationand self-reflection. Topics are discussed in andragogical, qualitative terms.